Adult idiopathic hypertrophic pyloric stenosis: an infrequent cause of gastric outlet obstruction - Khan, Nida; Kumar, Meena; Mahadik, Abhishek; Singhal, Pragati (International Surgery Journal, 2020)
Hypertrophic pyloric stenosis is a congenital disease, presenting within two weeks of birth. However adult idiopathic hypertrophic pyloric stenosis (AIHPS) presents in middle age, predominantly in males and usually without any antecedent cause. Secondary variant may be due to intra gastric causes or extra gastric post-operative adhesions. Patient presents with symptoms of gastric outlet obstruction. Diagnosis depends on clinical, radiological and endoscopic findings. Treatment is subtotal gastrectomy. Pyloroplasty and endoscopic dilatation may be tried in debilitated patients. We present a case of AIHPS presenting as gastric outlet obstruction in a 16 year old female, that was surgically managed with an antrectomy.